The cold war - Ziff, John (Broomall : Mason Crest, 2016)
Examines the events that led to the Cold War and political and military strategies employed by the United States and Soviet Union, and provides information on key people, battles, and events.
Chronology, notes, index and glossary
Juvenile
Keywords: Literature Juvenile works -- Literature Juvenile works